2015
DOI: 10.1007/s11547-014-0493-x
|View full text |Cite
|
Sign up to set email alerts
|

Non-mass-like lesions on breast ultrasound: classification and correlation with histology

Abstract: Non-mass-like breast lesions usually appeared as a hypoechoic area or a hypoechoic area with microcalcification. The finding of a hypoechoic area with microcalcification had a close correlation with malignant lesions. US had a high sensitivity but a low specificity in the diagnosis of non-mass-like breast lesions and a definitive diagnosis requires a US-guided biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
5
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 13 publications
1
43
5
5
Order By: Relevance
“…The correct kjronline.org that the retraction phenomenon, hyper-or hypoechoic rim, skipping sign, and white wall sign of the coronal plane were useful in distinguishing benign from malignant breast lesions. In this study, the incidence of NMLs was much lower than that of masses in consecutive women (18,19,21,23), with a rate of approximately 1:5 (80:377). Additionally, the coronal ABUS image features were correlated with the clinical factors according to lesion type.…”
Section: Diagnostic Value Of Coronal Featuresmentioning
confidence: 51%
See 1 more Smart Citation
“…The correct kjronline.org that the retraction phenomenon, hyper-or hypoechoic rim, skipping sign, and white wall sign of the coronal plane were useful in distinguishing benign from malignant breast lesions. In this study, the incidence of NMLs was much lower than that of masses in consecutive women (18,19,21,23), with a rate of approximately 1:5 (80:377). Additionally, the coronal ABUS image features were correlated with the clinical factors according to lesion type.…”
Section: Diagnostic Value Of Coronal Featuresmentioning
confidence: 51%
“…In contrast, a NML refers to a hypoechoic area lacking a conspicuous margin or shape and can be defined as a nonspace occupying lesion (17). Previous studies (18)(19)(20)(21)(22)(23) have reported some features that may aid in the identification of malignant NMLs, such as palpability, architectural distortion, and calcification. However, whether the coronal features can help to evaluate NMLs has not been discussed.…”
Section: Definition Of Image Type and Coronal Featuresmentioning
confidence: 99%
“…The reason for the difference might be that diagnostic criteria for non-mass-like lesions have not yet been established, standardized analysis of non-mass-like lesions cannot be performed, and the diagnosis of non-masslike lesions is susceptible to the subjectivity of sonographers. In fact, not only DCIS lesions, but also other malignant lesions and benign lesions can present as non-masslike lesions, such as infiltrating ductal carcinoma (IDC), lymphatic metastatic poorly differentiated adenocarcinoma, adenocarcinoma, acute lymphatic leukaemia, infiltrating lobular carcinoma (ILC), adenosis, intraductal papilloma and plasma cell mastitis (21,27). According to the results of previous studies, mottled and geographic patterns, architectural distortion, posterior acoustic shadowing, microcalcifications, older (postmenopausal) patient age, and a larger lesion size were more frequently associated with malignant non-mass-like lesions than benign non-masslike lesions (28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies based on B-mode, color Doppler ow imaging (CDFI), and strain or shear-wave elastography to distinguish benign from malignant NMLs have demonstrated their diagnostic performance. Similar to non-mass-like enhancement on breast MRI, with the enhanced image quality of high-resolution ultrasonography and widespread use of bilateral whole-breast examinations, it is possible to detect the hypoechoic regions (NMLs) that do not meet criteria for space-occupying lesions de ned by BI-RADS [12,13]. NMLs re ect a wide range of breast lesions, including benign, high-risk, and malignant lesions.…”
Section: Introductionmentioning
confidence: 99%